Functional characteristics of the rigid elytra in a bamboo weevil beetle Cyrtotrachelus buqueti - Xin Li; Yu Zheng (IET Nanobiotechnology)
Abstract The bamboo weevil beetle, Cyrtotrachelus buqueti, has evolved a particular flight pattern. When crawling, the beetle folds the flexible hind wings and stuffs under the rigid elytra. During flight, the hind wings are deployed through a series of deployment joints that are passively driven by flapping forces. When the hind wings are fully expanded, the unfolding joint realises self‐locking. At this time, the hind wings act as a folded wing membrane and flap simultaneously with the elytra to generate aerodynamics. The functional characteristics of the elytra of the bamboo weevil beetle were investigated, including microscopic morphology, kinematic properties and aerodynamic forces of the elytra. In particular, the flapping kinematics of the elytra were measured using high‐speed cameras and reconstructed using a modified direct linear transformation algorithm. Although the elytra are passively flapped by the flapping of the hind wings, the analysis shows that its flapping wing trajectory is a double figure‐eight pattern with flapping amplitude and angle of attack. The results show that the passive flapping of elytra produces aerodynamic forces that cannot be ignored. The kinematics of the elytra suggest that this beetle may use well‐known flapping mechanisms such as a delayed stall and clap and fling.